2002
DOI: 10.1002/cbf.972
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exogenous fatty acids and cholesterol on aminopeptidase activities in rat astroglia

Abstract: Several studies have addressed the interaction between fatty acids and lipids with central nervous system peptides. Because aminopeptidases (AP) are involved in the regulation of neuropeptides, this work studies several AP expressed in cultured astroglia, after exogenous addition of oleic and linoleic fatty acids and cholesterol to the culture medium. Alanyl-AP, arginyl-AP, cystyl-AP, leucyl-AP, tyrosyl-AP and pyroglutamyl-AP activities were analysed in whole cells using the corresponding aminoacyl-beta-naphth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…These biochemical changes can be accompanied by alterations in the physical state of the membrane, for example in membrane fluidity (39). Moreover, the addition of C18:1 cis and C18:2 to cultured astrocytes decreases several aminopeptidase activities (17). Furthermore, it has been shown that C18:1 cis addition determines a dosedependent inhibition of GAP junction permeability in cultured rat astrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These biochemical changes can be accompanied by alterations in the physical state of the membrane, for example in membrane fluidity (39). Moreover, the addition of C18:1 cis and C18:2 to cultured astrocytes decreases several aminopeptidase activities (17). Furthermore, it has been shown that C18:1 cis addition determines a dosedependent inhibition of GAP junction permeability in cultured rat astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that exogenous fatty acids may influence the fatty acid composition of neuronal and glial membranes (10)(11)(12)(13)(14), and these changes in turn can affect cellular metabolism and regulatory (15) and inflammatory processes (16). Furthermore, in primary cultures of rat astroglia, it has been shown that the addition of oleic and linoleic acids to the medium reduces several aminopeptidase activities (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, Murphy (1995) has demonstrated that cultured astrocytes take up exogenous linoleic acid and incorporate its metabolites into phospholipids, and that the resulting changes in membrane fatty acid composition modify certain specific cell function properties. These chemical changes can be accompanied by changes in the physical state of the membrane, and could be responsible for the effects of fatty acids on RAS-regulating activities reported (Ramirez-Exposito et al, 2002). Moreover, it is well known that changes in the relative amounts of free fatty acids in the cellular membrane may be major factors in the physiological role of the membrane by changing membrane fluidity.…”
Section: Olive Oil Intake High Cholesterol Intake Commentsmentioning
confidence: 98%
“…In fact, these fatty acids have been shown to lower arterial pressure in various models of experimental hypertension (Hui et al, 1991). Using primary cultured astroglia, we have described (Ramirez-Exposito et al, 2002) that the addition of oleic and linoleic fatty acids to the culture medium decreases, to different degrees, several RAS-regulating angiotensinases, whereas the presence of exogenous cholesterol in the medium increases them. Thus, our results showed a significant decrease of GluAP activity after incubation with oleic and linoleic fatty acids, which may indicate the existence of high levels of Ang II.…”
Section: Tissue Rasmentioning
confidence: 99%